2012
DOI: 10.1111/j.1557-9263.2012.00387.x
|View full text |Cite
|
Sign up to set email alerts
|

Island shape, size, and isolation affect nest-site selection by Little Terns

Abstract: Populations of many seabirds and other species that nest along coasts are declining due to habitat degradation and loss. An improved understanding of the species‐specific factors that determine nest density across a landscape is therefore critical for conservation efforts. We examined factors that affected the density (number per hectare) and abundance (number at a sampling site) of nests of Little Terns (Sternula albifrons) on the Sinai Peninsula, Egypt. Terns preferred to nest on islands rather than the main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
11
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 33 publications
2
11
1
Order By: Relevance
“…Thus, small islands averaged similar nest numbers compared to large islands. Previous studies have reported that some waterbirds nest in greater numbers on small‐ to intermediate‐sized islands compared to large islands, perhaps to avoid predators large islands may harbor (Erwin et al , Eason et al ). We suspect that preference for nesting near water exhibited by avocets, stilts, and terns contributed to similar numbers of nests between large and small islands.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, small islands averaged similar nest numbers compared to large islands. Previous studies have reported that some waterbirds nest in greater numbers on small‐ to intermediate‐sized islands compared to large islands, perhaps to avoid predators large islands may harbor (Erwin et al , Eason et al ). We suspect that preference for nesting near water exhibited by avocets, stilts, and terns contributed to similar numbers of nests between large and small islands.…”
Section: Discussionmentioning
confidence: 99%
“…Nest abundance was predicted to be almost 3 times greater on an island with a shape index of 3.0 (i.e., island roughly 34 times longer than wide) relative to a round island (shape index of 0.9). Previous studies have reported that many waterbirds, including terns and shorebirds, often nest within a few meters of the water's edge (Cuervo , Stenhouse et al , Maxson et al , Eason et al ). In a companion study, we report that the probability of nesting peaked on island patches that were 2 m and 7 m from the water among terns and avocets, respectively (Hartman et al ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…34. The topography of the area destroyed will impact the kind and rate of recovery (Cox and Cox 1977;Eason et al 2012). 35.…”
mentioning
confidence: 99%